Magnetoreception in Social Wasps: An Update - Pereira-Bomfim, Maria da Graça Cardoso; Antonialli-Junior, William Fernando; Acosta-Avalos, Daniel (EntomoBrasilis, 2016)
Abstract. Magnetoreception is a mechanism of active orientation that occurs in animals with nervous systems. Social insects such as bees, ants, wasps and termites have been studied on the influence of the magnetic field exerts on its biology. The social wasps comprise species represented in Stenogastrinae, Vespinae and Polistinae, however studies on the influence of magnetic field on wasps Vespinae address only. The areas studied include the biomineralization of magnetic material and behavioral aspects related to changes in local intensity of the geomagnetic field. The objective of this review is to integrate knowledge of social wasps’ magnetoreception in order to build an instructive overview of the current situation of studies, therefore, provide the conceptual framework for the development of future work on the topic. Magnetorrecepção em Vespas Sociais: Uma Atualização Resumo. Magnetorrecepção é um mecanismo de orientação ativa que ocorre em animais com sistema nervoso. Insetos sociais tais como abelhas, formigas, vespas e cupins são estudados sobre a influência que o campo magnético exerce em sua biologia. As vespas sociais compreendem espécies representadas em Stenogastrinae, Vespinae e Polistinae, no entanto os estudos sobre a influência do campo magnético em vespas abordam somente Vespinae. As áreas de estudo incluem a biomineralização do material magnético e aspectos comportamentais relacionados a mudanças na intensidade do campo geomagnético local. O objetivo desta revisão é integrar o conhecimento sobre magnetorrecepção em vespas sociais, a fim de construir um panorama elucidativo da atual situação dos estudos, e assim fornecer uma estrutura conceitual para o desenvolvimento de trabalhos futuros sobre o tema.